2021
DOI: 10.3390/brainsci11091132
|View full text |Cite
|
Sign up to set email alerts
|

Brain–Immune Interactions as the Basis of Gulf War Illness: Clinical Assessment and Deployment Profile of 1990–1991 Gulf War Veterans in the Gulf War Illness Consortium (GWIC) Multisite Case-Control Study

Abstract: The Boston University-based Gulf War Illness Consortium (GWIC) is a multidisciplinary initiative developed to provide detailed understanding of brain and immune alterations that underlie Gulf War illness (GWI), the persistent multisymptom disorder associated with military service in the 1990–1991 Gulf War. The core GWIC case-control clinical study conducted in-depth brain and immune evaluation of 269 Gulf War veterans (223 GWI cases, 46 controls) at three U.S. sites that included clinical assessments, brain im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…Overall, our findings are consistent with previous studies of Gulf War veterans that have identified pesticides and use of PB/NAPP pills as the most prominent risk factors for GWI, after adjusting for other exposures in theater [1,7,[21][22][23][24], as well as with individual types of symptoms and symptom domains [7,[25][26][27]]. An association between GWI and indicators of possible exposure to chemical weapons during the Gulf War has, overall, been less consistent [1,7].…”
Section: Discussionsupporting
confidence: 86%
“…Overall, our findings are consistent with previous studies of Gulf War veterans that have identified pesticides and use of PB/NAPP pills as the most prominent risk factors for GWI, after adjusting for other exposures in theater [1,7,[21][22][23][24], as well as with individual types of symptoms and symptom domains [7,[25][26][27]]. An association between GWI and indicators of possible exposure to chemical weapons during the Gulf War has, overall, been less consistent [1,7].…”
Section: Discussionsupporting
confidence: 86%
“…Findings from our study revealed that older age was associated with lower odds of meeting the GWI phenotypes than younger age. Although this association has been reported in other studies of deployed GW veterans [6,10,24], in this current study, somewhat surprisingly, this finding held in both non-deployed and deployed samples-even after adjusting for military rank during the war. Previous explanations for the observed relationship between younger age and greater risk of GWI included the lower educational attainment of the younger servicemembers at the time of the deployment, their relative inexperience and sense of control during deployment reflected in their lower military rank, and their greater likelihood of being directly exposed to deployment-related toxins that may be associated with GWI.…”
Section: Discussioncontrasting
confidence: 70%
“…Today, approximately 30% or 200,000 of Gulf War veterans remain affected by the persistent and largely unexplained physical symptoms collectively known as Gulf War Illness (GWI; Maule et al, 2018). Although a recent study linked the chronic symptoms to brain and inflammatory alterations triggered by combined deployment exposures or toxic wounds (Steele et al, 2021), more research is needed to fully understand the pathophysiology of GWI given varying locations of deployment and exposure. In addition, despite years of scientific investigations, an accepted unified case definition for GWI is lacking as are viable and effective treatments and definitive guidelines for healthcare providers (Baldwin et al, 2019; Kaimal & Dieterich-Hartwell, 2020).…”
Section: Introductionmentioning
confidence: 99%